2010
DOI: 10.4103/0970-9290.70814
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and acceptability of 0.074% diclofenac-containing mouthwash after periodontal surgery: A clinical study

Abstract: The new 0.074% diclofenac mouthwash is an effective and tolerable medicinal product for post-surgical symptomatic relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…NSAIDs reduce the production of prostaglandins[ Table 1]that sensitize nerve endings at the site of injury. Clinical trials have shown that NSAIDs are effective in the management of any level of dental pain, whether mild, moderate or severe 13 .The most commonly used topical analgesics in oral mucosal pain are choline salicylate, benzydamine, benzalkonium chloride and diclofenac sodium.…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
See 1 more Smart Citation
“…NSAIDs reduce the production of prostaglandins[ Table 1]that sensitize nerve endings at the site of injury. Clinical trials have shown that NSAIDs are effective in the management of any level of dental pain, whether mild, moderate or severe 13 .The most commonly used topical analgesics in oral mucosal pain are choline salicylate, benzydamine, benzalkonium chloride and diclofenac sodium.…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
“…3% diclofenac in 2.5% hyaluronan was an effective treatment for common, painful disorder Recurrent aphthous stomatitis according to Iraji et al 16 . Sangita et al showed that 0.074% diclofenac mouthwash is an effective and tolerable medicinal product for post-surgical symptomatic relief 13 .VOLINI GEL ® (DiclofenacDiethylamine BP 1.16% w/w) is indicated for relief from pain, swelling and inflammation due to joint pain, low back pain, neck pain & shoulder pain, minor sports injury, sprains & sprains. In dentistry it is used to relieve pain caused by tempromandibular disorders.…”
Section: Figure4 Mechanism Of Action Of Nsaidsmentioning
confidence: 99%
“…Diclofenac mouthwash is useful in administration for postoperative pain after periodontal surgery [7][8][9] and shows a very good safety in the treatment 8,10 . This medicine showed positive results on pharyngodynia and odynophagia 11 , in symptomatic relief in all types of aphthous ulceration 12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the systemic use of these drugs is commonly associated with side effects, impairing patients’ compliance to their consumption [16]. Although the local utilization of NSAIDs and other anti-inflammatory agents has been examined in some studies, many of them have revealed unsatisfactory results in controlling inflammation when these drugs are topically administrated [17-19]. …”
Section: Introductionmentioning
confidence: 99%